COVID-19, gender and estroprogestins, what do we know?. (2nd January 2022) - Fidecicchi, Tiziana; Fruzzetti, Franca; Lete Lasa, Luis Ignacio; Calaf, Joaquim
Abstract: The new coronavirus disease-19 (COVID-19) pandemic has rapidly spread all around the world, eliciting many questions and doubts about the pathogenesis of the disease and treatment. Mortality has been related to a prothrombotic state. Risk factors for the infection and for severe forms of COVID-19 have still to be defined. According to data collected, women appear to be less prone to severe forms of the disease and their mortality was lower than for men. The role of female hormones in the modulation of inflammation may be the reason behind this gender gap. Considering the prothrombotic state activated by the virus, hormone therapies have been placed under investigation as possible increasing risk factors for severe forms. Moreover, new vaccines and their rare thrombotic side effects have increased the concern about this issue. The goal of this review is to go over the mechanisms that lead up to thrombosis during COVID-19, trying to explain the possible reasons why women seem to be naturally protected. The expert opinions about whether to continue/discontinue hormonal therapies are reviewed. Moreover, available data about the so-called 'vaccine induced immune thrombotic thrombocytopaenia' caused by vaccines against COVID-19 are discussed.